The effect of workload on employee performance at the bpjs claim unit at sundari general hospital in 2022 - Rahmawati tarigan; Yulida Effendi Nasution; Sri Agustina Meliala (Institute of Computer Science (IOCS), 2023)
Employee performance services at the BPJS Claim Unit at the hospital cannot be separated from the patient, because with the classification the patient feels more valued according to his rights and it can be seen how the conditions and workload of employees at the BPJS Claim Unit are. This type of research is qualitative research using a case study approach (Case Study) to find out and identify how workload influences work on employee performance at the BPJS Claim Unit at Sundari General Hospital in 2022 which was carried out from January to October 2022. There were 4 informants in this study, namely 3 main informants and 1 triangulation informant. The research results show that the implementation of the job descriptions of the BPJS Claim Unit still overlaps so that it affects employee performance. The workload at the BPJS Claim Unit is not proportional to the number of existing officers which causes the implementation of the BPJS Claim Unit tasks to be less than optimal. The conclusion The BPJS Claim Unit workload affects the performance of the BPJS Claim Unit job descriptions which still have constraints, namely the facilities and infrastructure as well as the human resources. The advice given is that it is better to improve the quality of human resources, add more educated employees according to the qualifications of the BPJS Claim Unit and improve infrastructure and human resources in the BPJS Claim Unit.